Should You Meet the Parents? The Impact of Information on Non-test Score Attributes on School Choice - Elisa Facchetti; Lorenzo Neri; Marco Ovidi (Institute of Labor Economics (IZA), 2023)
Understanding parental response to non-test score attributes is crucial to design effective school choice systems. We study an intervention providing parents with hard-to-find information on the school environment while holding information on school performance constant. The provision of this information decreases the outflow to private institutions by 17% and increases enrollment at local state schools, particularly among high-income and high-performing students. This intervention encourages parents to expand their state-school search without affecting their taste for academic performance, generating increased competition for schools with desirable attributes. These findings imply that simple, low-cost interventions may improve state schools' finances and composition.
Keywords: I24; I28; H75; 330; school choice; non-test score school attributes; information intervention